Effects Of Ultraviolet Irradiation On The Physicochemical And Functional Properties Of Selected Food Biopolymers - Kuan , Yau Hoong (2011)
The application of food biopolymers can be diversified with chemical, enzymatic or physical modifications. This thesis addressed the use of ultraviolet (UV) irradiation to modify the functional properties of selected food biopolymers. These food biopolymers include food proteins derived from plant sources, specifically soy protein isolate (SPI) and wheat gluten (WG) as well as food proteins derived from animal sources, specifically egg white protein (EW) and sodium caseinate (SC). Other than this, food biopolymer from polysaccharides, specifically gum arabic (GA) was also selected. In this study, the effects of UV irradiation on the physicochemical and functional properties of selected food biopolymers were investigated, particularly on the emulsifying and foaming properties.